Shared and contested meanings in the Mindanao conflict - de Guzman, Judith M.; Inzon, Charlie M. (Philippine Journal of Psychology, 2011)
"This research focused on the meanings of Bangsamoro, a concept that lies at the heart of the Mindanao conflict in Southern Philippines."